Regio- and Stereocontrolled Nucleophilic Trifluoromethylthiolation of Morita–Baylis–Hillman Carbonates - Dai, Xiaoyang; Cahard, Dominique (Synlett, 2015)
Reactions of Morita–Baylis–Hillman carbonates with metal-free sources of trifluoromethylthio anion have been studied. The combination of CF3SiMe3/S8/KF/DMF gave the primary allylic SCF3 products through apparent SN2′ reaction whereas the use of Zard’s reagent, CF3SCO2C18H37, allowed us to intercept the fleeting secondary allylic SCF3 product.
Keywords: fluorine; sulphur; Morita–Baylis–Hillman adduct; substitution; stereocontrol